2022
DOI: 10.3389/fphys.2022.838069
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cytokines Concentration Following Long-Distance Running: A Systematic Review and Meta-Analysis

Abstract: Long-distance running is an exhausting effort for the whole organism. Prolonged aerobic exercise induces changes in inflammatory markers. However, predicting muscle damage in response has limitations in terms of selecting biomarkers used to measure inflammatory status. The present study conducts a systematic review and meta-analysis of articles focusing in ultra-marathon, marathon, and half-marathon and levels of cytokines. The search was conducted in PubMed, Web of Science, and Scopus databases, resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 127 publications
(556 reference statements)
2
21
0
Order By: Relevance
“…In addition to the modulation of immune microenvironment, physical activity ameliorates immunosenescence through promoting the secretion of several cytokines by skeletal muscle during physical activity, including IL-6, IL-7 and IL-15 [ 26 ]. Similarly, a meta-analysis conducted by Micael Deivison de Jesus Alves, et al found that long-distance running was associated with increased levels of IL-6, IL-1ra, IL-1β, IL-8, IL-10, and TNF-α, and with decreased levels of IL-2, and IFN-γ [ 40 ]. In general, physical activity has immune-promoting effect, which may facilitate the anti-tumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the modulation of immune microenvironment, physical activity ameliorates immunosenescence through promoting the secretion of several cytokines by skeletal muscle during physical activity, including IL-6, IL-7 and IL-15 [ 26 ]. Similarly, a meta-analysis conducted by Micael Deivison de Jesus Alves, et al found that long-distance running was associated with increased levels of IL-6, IL-1ra, IL-1β, IL-8, IL-10, and TNF-α, and with decreased levels of IL-2, and IFN-γ [ 40 ]. In general, physical activity has immune-promoting effect, which may facilitate the anti-tumor immune response.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, strenuous exercise augments adiponectin levels or does not affect them at all [ 54 , 55 , 67 , 75 ]. Conversely, others reported a reduction in serum adiponectin levels after five repeated WAnTs in sedentary young adults [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that intense physical activity leads to an increase in circulating IL-6 levels [ 55 ], especially after prolonged strenuous exercise, such as a marathon run [ 75 ]. Surprisingly, in the current study, we did not observe any changes in IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the sample size was calculated based on IL-6 due to the fact that this molecule is the most evaluated cytokine/myokine in studies involving a strenuous and prolonged exercise session, as reported by Alves et al ( 2022 ). In addition, we emphasize that we use the G * Power software and the data obtained in the study developed by Nieman and collaborators (Nieman et al, 2005 ), and based on a maximum permissible error margin of 5% and a sampling power of 0.95, the minimum sample size calculated were 10 subjects.…”
Section: Discussionmentioning
confidence: 99%